Three dimensional mechanical model to simulate the NSM FRP strips shear strength contribution to a RC beam: parametric studies - Bianco, V. (2012)
This paper presents the results of a parametric study carried out with a a mechanical model recently developed to simulate the shear strength contribution provided by a system of Near Surface Mounted (NSM) Fiber Reinforced Polymer (FRP) strips applied to a Reinforced Concrete (RC) beam. That model, developed fulfilling equilibrium, kinematic compatibility and constitutive laws of both materials, concrete and FRP, and local bond between themselves, takes into consideration the possibility that the NSM strips may fail due to: loss of bond (debonding), concrete semi-conical tensile fracture or strip tensile rupture. The model also takes into consideration: a) interaction between progressive force transferred by bond to the surrounding concrete and its tensile fracture and b) bi-directional interaction among adjacent strips placed on the two sides of the strengthened beam cross-section web. In the first part of the paper attention is focused on the bond-based behavior of a single NSM FRP strip mounted on a concrete prism. The influence of each geometrical-mechanical parameter on the peak force transferable through bond stresses to the surrounding concrete, excluding the possibility of either concrete fracture and strip rupture, is analyzed. In the second part of the paper attention is focused on the comprehensive behavior of a single NSM FRP strip mounted on a concrete prism. The influence of each geometrical-mechanical parameter on the peak force transferable to the surrounding concrete, also including the possibility of both concrete fracture and strip rupture, is analyzed. The third part of the paper is devoted at assessing the influence of each geometrical-mechanical parameter on the maximum shear strength contribution provided by a system of NSM FRP strips applied to a RC beam. The results of these studies are presented along with the main findings.